Gioco del calcio, «poesia dei campi verdi» e infanzia. Testi e autori Chiara Lepri - Lepri, Chiara (Studi sulla Formazione/Open Journal of Education, 2023)
The paper aims to investigate the presence of the representation of the sport of football in Italian poetry and the themes and motifs through which it recurs. In particular, through the literary evidence of poets such as Saba, Sereni, Giudici, Caproni, Pasolini, Spaziani, Porta, Raboni and others, a very suggestive path along which literature and football meet is highlighted: the two human activities originate from a certain amount of creativity; both allude to a human and historical dimension; both, finally, are connected to aesthetic pleasure and the dimension of play. Finally, we can see a triadic circularity between football, play and childhood, well expressed by poets such as Alfonso Gatto and Gianni Rodari. The path traced, which intercepts the feeling of the youngest on a terrain of consonances, but also of experiences and passions, can allow our youngsters to develop a renewed pleasure and enthusiasm in their relationship with the poetic text.